Pengembangan dan Penataan yang Setara Berkeadilan Terhadap Minimarket di Kota Pekanbaru berdasarkan Peraturan Daerah Kota Pekanbaru Nomor 09 Tahun 2014 Tentang Pengelolaan Pasar Rakyat, Pusat Perbelanjaan dan Toko Swalayan - Yalid (Faculty of Law Hang Tuah University, 2016)
This research aims to describing and analyzing the equal and fair development and arrangement of minimarket in Pekanbaru based on Regional Regulation of Pekanbaru City No. 09 of 2014 on the Management of People's Market, Shopping Center and Supermarket; and explaining the obstacles and efforts to overcome the equal and fair development and arrangement of minimarket in Pekanbaru City. The research method is socio-legal research. The conclusion of the research is that based on the Regional Regulation No. 09 of 2014, the establishment of minimarket shall be based on RTRW, RDTRK, and zoning regulations; and that developing and arranging minimarket equally and fairly in Pekanbaru City still meet some obstacles. To overcome the obstacles, the Government of Pekanbaru City has carried out some efforts, so that the equal and fair development and arrangement of minimarket in Pekanbaru City can continuously run well.